Estimation of Homocysteine Level in Sudanese Obese, Gezira State, Sudan - Abdelazeem, Hala; Mergani, Adil; Mohammed, Yousif Abdelhameed; Ahmaed, Khalid Abdelsamea M.; Nour, Bakri Yousif Mohamed (British Journal of Healthcare and Medical Research, 2022)
Science-based evidence on the association of total homocysteine (Hcy) with body mass index (BMI), as well as obesity and elevated Hcy levels, in the general population has been conflicted .The primary goals of this case control study is to evaluate the relationship between Hcy concentration and obesity in Gezira state in Sudan. A total of 221 participants including 140 obese , their average age was 49.49±12.2 years, divided into three groups on the basis of BMI according to the WHO classification and the groups constituted 44 obese type I , 51 obese type II and 45 obese type III , the control group was normal weight (BMI < 25.9) include 81 participants ,their age medium were 45.78±22.38 years .Three mL of venous blood from each participant was collected in the morning after a twelve hours overnight fasting in lithium heparin container, then the separated plasma was stored at −80 ◦C for further analysis. Serum Hcy was measured using the enzymatic method by Cobas C 411analyzer. The cut-off value for normal levels of Hcy is 15 μmol/L , out of 140 obese, there were 43(30.7%) having hyperhomocysteinemia (HHcy).The Hcy average increased in obese (12.65±4.9) in comparing with control(10.45±3.8) giving significant difference (P value 0.002). The mean values of Hcy were also compared among the various obesity types. It was found that there was no statistically significant (P value0.628). Pearson correlation analyses showed that BMI was negatively associated with Hcy (r-0.027, P value 0.754). The mean of Hcy was decreased in the lower age group (20 – 40 years), and increased in the higher age group (61 – 80years) showing no significant difference but age is positively correlated with high level of Hcy (r 0.094, P value: 0.268). The study finding showed significant relationship between Hcy and obesity. However, the Hcy concentrations were not positively correlated with the degree of obesity, further studies are needed to ascertain the causal role of Hcy in the development of obesity and to explore how Hcy is involved in the pathogenesis of obesity.